2016
DOI: 10.1007/978-3-319-22533-3_63
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Precision, Sensitivity, and Specificity of Noninvasive ICP Absolute Value Measurements

Abstract: An innovative absolute intracranial pressure (ICP) value measurement method has been validated by multicenter comparative clinical studies. The method is based on two-depth transcranial Doppler (TCD) technology and uses intracranial and extracranial segments of the ophthalmic artery as pressure sensors. The ophthalmic artery is used as a natural pair of "scales" that compares ICP with controlled pressure Pe, which is externally applied to the orbit. To balance the scales, ICP = Pe a special two-depth TCD devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…this method was reported to have better diagnostic reliability for detecting elevated ICP compared to optic nerve sheath diameter measurement [66][67][68][69]. An independent clinical validation study determined that this technique had a fair agreement to ICP measured using lumbar puncture [70].…”
Section: Plos Onementioning
confidence: 97%
“…this method was reported to have better diagnostic reliability for detecting elevated ICP compared to optic nerve sheath diameter measurement [66][67][68][69]. An independent clinical validation study determined that this technique had a fair agreement to ICP measured using lumbar puncture [70].…”
Section: Plos Onementioning
confidence: 97%
“…Ragauskas et al [ 161 , 162 , 163 , 164 ] introduced a two-depth Doppler approach with excellent accuracy and reliability in initial studies (including a Bland–Altman-Plot). The approach uses a preocular, extracranial pressure chamber, as well as a two-depth transorbital Doppler aimed at the intracranial and extracranial segment of the ophthalmic artery.…”
Section: Approaches Of Non-invasive Measurementsmentioning
confidence: 99%
“…A follow-up study examined a group of 62 patients of various neurologic conditions (primarily idiopathic intracranial hypertension and multiple sclerosis) with invasively measured ICP by lumbar puncture and found a bias that was not statistically different from zero, with a standard deviation of error of 2.19 mm Hg, indicating a high level of precision [51]. Several other papers have seemingly confirmed a negligible bias in a variety of conditions [52,53]. Another paper investigated the classification efficacy of the TDTD technique by comparing it to the optic nerve sheath diameter (ONSD) method (described below) in a group of neurological patients (85 patients enrolled in TDTD and 92 in ONSD) requiring lumbar puncture and concluded that the TDTD method has better diagnostic reliability for detecting elevated ICP [54].…”
Section: Two-depth Ophthalmic Artery Doppler Ultrasonographymentioning
confidence: 99%